2022
DOI: 10.1177/22799036221123961
|View full text |Cite
|
Sign up to set email alerts
|

Psoriasis in Northern Saudi Arabia: Clinical features and implications for quality of life

Abstract: Introduction: Psoriasis is a chronic non-contagious inflammatory skin disorder, which might impair patient’s social relationships, limit leisure activities, and lower self-esteem. Psoriasis patients might be stigmatized leading to psychological disorders such as anxiety and depression. Objectives: This study aimed to outline the clinical features of psoriasis and its effects on quality of life, and the feeling of stigmatization among psoriasis patients. Methods: This cross-sectional questionnaire-based study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…The present study revealed that that 68% of the studied cases had gradual onset of disease, 62.9% with progressive course and median duration of disease was 6 years ranging from 1 to 40 years. Other studies (23)(24)(25) found that most of psoriatic cases had gradual onset (96%) and 32% were progressive. The median duration of psoriasis was 18 years (26) .…”
Section: Discussionmentioning
confidence: 89%
“…The present study revealed that that 68% of the studied cases had gradual onset of disease, 62.9% with progressive course and median duration of disease was 6 years ranging from 1 to 40 years. Other studies (23)(24)(25) found that most of psoriatic cases had gradual onset (96%) and 32% were progressive. The median duration of psoriasis was 18 years (26) .…”
Section: Discussionmentioning
confidence: 89%
“…Of the studied cases; 86.7% are married versus 80% of control group. In addition, Bayomy et al [12] had examined 109 cases with PV whose ages were ranging from 18 to 66 years. The percentage of male to female ratio was 41.28/58.72%.…”
Section: Discussionmentioning
confidence: 99%